Stress phase angle depicts differences in arterial stiffness: phantom and in vivo study. (14th May 2015) - Niu, Lili; Meng, Long; Xu, Lisheng; Liu, Jia; Wang, Qiwen; Xiao, Yang; Qian, Ming; Zheng, Hairong
Abstract: The endothelial cells (ECs) lining of a blood vessel wall are exposed to both the wall shear stress (WSS) of blood flow and the circumferential strain (CS) of pulsing artery wall motion. Both WSS and CS keep involved in the modulation of ECs' biochemical response and function and the temporal phase angle between the two is called stress phase angle (SPA). Previous studies at the cellular level have indicated that SPA is highly negative at sites that are prone to atherosclerosis, and hypothesized that large SPA may contribute to atherogenesis. Till now, there is no experimental data to support this hypothesis, probably due to the lack of a proper tool for measuring WSS and CS simultaneously and real time. In this study, a non-invasive ultrasonic biomechanics method was utilized to quantitatively calculate the SPA and experimentally evaluate the role of SPA in predicting early atherosclerosis. Three silicon tubes with a stiffness of 1.15, 3.62, 9.38 MPa were assembled in a pulsatile flow circuit and the values of SPA were measured to be −101.86 ± 3.65°, −170.19 ± 17.77° and −260.63 ± 18.62°, respectively. For the PVA-c phantoms, stiffness was 162.45, 235.68 and 374.24 kPa, the SPA corresponding to −170.32 ± 17.55°, −207.56 ± 10.78° and −261.08 ± 10.90°, respectively. Both phantom studies results demonstrated that SPA was highly negative in stiffer arteries. Further, experiments were taken in healthy living rats as control group ( n = 3), atherosclerotic model group ( n = 3), and drug treated group ( n = 3), and the results showed that SPA was most negative in the model group, and SPA was least negative in the control group. Together, this study suggested that highly negative SPA appeared to be a prominent mechanical feature of vessels prone to atherosclerotic disease.